Impact of low-volume concurrent strength training distribution on muscular adaptation. Issue 10 (October 2020) - Kilen, Anders; Bay, Jonathan; Bejder, Jacob; Breenfeldt Andersen, Andreas; Bonne, Thomas Christian; Larsen, Pernille Dyeremose; Carlsen, Andreas; Egelund, Jon; Nybo, Lars; Mackey, Abigail Louise; Olsen, Niels Vidiendal; Aachmann-Andersen, Niels Jacob; et al.
Abstract: Objectives: Military-, rescue- and law-enforcement personnel require a high physical capacity including muscular strength. The present study hypothesized that 9 weeks of volume matched concurrent short frequent training sessions increases strength more efficiently than less frequent longer training sessions. Design: A randomized training intervention study with functional and physiological tests before and after the intervention. Methods: Military conscripts ( n = 290) were assigned to micro-training (four 15-min strength and four 15-min endurance bouts weekly); classical-training (one 60-min strength and one 60-min endurance training session weekly) or a control-group (two 60-min standard military physical training sessions weekly). Results: There were no group difference between micro-training and classical-training in measures of strength. Standing long jump remained similar while shotput performance was reduced ( P ≤ 0.001) in all three groups. Pull-up performance increased ( P ≤ 0.001) in micro-training (7.4 ± 4.6 vs. 8.5 ± 4.0 repetitions, n = 59) and classical-training (5.7 ± 4.1 vs. 7.1 ± 4.2 repetitions, n = 50). Knee extensor MVC increased ( P ≤ 0.01) in all groups (micro-training, n = 30, 11.5 ± 8.9%; classical-training, n = 24, 8.3 ± 11.5% and control, n = 19, 7.5 ± 11.8%) while elbow flexor and hand grip MVC remained similar. Micro-training increased ( P ≤ 0.05) type IIa percentage from 32.5 ± 11.0% to 37.6 ± 12.3% ( n = 20) and control-group increased ( P ≤ 0.01) type IIax from 4.4 ± 3.0% to 11.6 ± 7.9% ( n = 8). In control-group type I, fiber size increased ( P ≤ 0.05) from 5121 ± 959 μm to 6481 ± 2084 μm ( n = 5). Satellite cell content remained similar in all groups. Conclusions: Weekly distribution of low-volume concurrent training completed as either eight 15-min bouts or two 60-min sessions of which 50% was strength training did not impact strength gains in a real-world setting.